ANALYSIS DETERMINANTS OF RIAU PROVINCE'S EXPORT VALUE: GRAVITY MODEL APPROACH - Diana, Rahma (Politeknik Negeri Bengkalis, 2024)
Exports are an important part of international trade because they can make a very significant contribution to the economy of Riau Province. There are differences in the export value obtained by Riau Province based on the export destination country. The aim of this research is to analyze the influence of economic distance, population, GDP, REER and FDI of the destination country on the export value of Riau Province. The data used is panel data starting from 2011-2021 with a cross section of the main export destination countries, namely Japan, China, India, South Korea, Malaysia, the United States, the Netherlands. The analytical method used is the gravity model approach with random effect model techniques using Eviews 12 software. Analysis results: the economic distance and REER variables have a negative and significant effect on the export value of Riau Province while the population, GDP and FDI variables have a positive and significant effect on the export value of Riau Province. The suggestion is that government policy should be able to encourage the growth of foreign direct investment, and BI should also pay attention to policies regarding the rupiah exchange rate and then for future researchers to also carry out research on various superior commodities and other variables .